COGNITIVE ACTIVITY IN THE RESPECT OF QEEG RESEARCH - PRESENTATION OF LABORATORY TESTS - Prauzner, Tomasz; Prauzner, Małgorzata; Prauzner, Kacper; Ptak, Paweł (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article presents the methodology of laboratory tests carried out in the Laboratory of Experimental Research Biofeedback of the Jan Dlugosz University in Czestochowa (Poland) regarding the evaluation of education effectiveness by registering brain wave activity using electroencephalographic research (EEG method). The research results indicate that, depending on the form of the computer program visualization, a change in the activity of SMR, Beta1, Beta2 and Gamma waves was observed. The results are presented in the form of graphs and 2D brain activity images using the equipment Mitsar EEG 202 and WinEEG software